Effect of Ti Content on Structural Properties and Sensing Performance of Sol-Gel Synthesized PrTixOy Sensing Membranes. Issue 7 (6th May 2017) - Pan, Tung-Ming; Tan, Chia-Ying
Abstract : In this paper, we investigate the effect of titanium content on the structural properties and sensing characteristics of PrTix Oy sensing membranes using sol-gel processing for electrolyte-insulator-semiconductor (EIS) pH sensors. X-ray diffraction, Auger electron spectroscopy, X-ray photoelectron spectroscopy, and atomic force microscopy were used to study the film structures, elemental depth profiles, chemical compositions, and surface morphologies of these membranes, respectively, as a function of the growth condition (Ti solution concentrations of 0.3, 0.4 and 0.5 M). The PrTix Oy EIS device prepared at the Ti concentration of 0.4 M exhibited the best sensing characteristics (pH sensitivity, hysteresis voltage and drift rate). We attribute this behavior to the optimal titanium content in the sensing membrane forming a stoichiometric Pr2 Ti2 O7 film and increasing its surface roughness.